2021
DOI: 10.3991/ijes.v9i4.26995
|View full text |Cite
|
Sign up to set email alerts
|

The Influence E-Learning Platforms of Undergraduate Education in Iraq

Abstract: continue learning. Technology has become not only an activity but also a fundamental tool. Moreover, technology becomes the core media that allows education to happen. In Iraq Blended Learning used to overcome the pandemic and counting education Therefore, the use of computers and digital applications became part of daily life and for long hours. Therefore, properly designed digital educational activities linked to social media have become a powerful educational tool aimed at finding ways of effective learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…To answer the second question of this study, mean scores and standard deviations for the students' responses to each of the questionnaire items 8−27 were calculated, as shown in Table 6. The results presented in Table 6 revealed that the arithmetic mean of all questionnaire items (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) for the AU was (3.37), with a standard deviation of (1.36), while for the GU it was (3.35), with a standard deviation of (1.44). This finding means that student satisfaction with the university's teaching and learning process at Ajman University and Griffith University during the COVID-19 pandemic is at a Moderate level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To answer the second question of this study, mean scores and standard deviations for the students' responses to each of the questionnaire items 8−27 were calculated, as shown in Table 6. The results presented in Table 6 revealed that the arithmetic mean of all questionnaire items (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) for the AU was (3.37), with a standard deviation of (1.36), while for the GU it was (3.35), with a standard deviation of (1.44). This finding means that student satisfaction with the university's teaching and learning process at Ajman University and Griffith University during the COVID-19 pandemic is at a Moderate level.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a certain degree of Self-guiding is required to pass an online class. Online learning, according to [14,[30][31][32], is a form of distance education in which technology mediates the learning process, teaching is provided entirely via the internet, and learners and teachers are not required to be present at the same time and location. Luyt [33] pointed out that features of online learning like access to the internet and the flexibility of online classes have made online learning an essential component of the learning system in higher education institutions.…”
Section: Online Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the COVID-19 pandemic situation has been a great advantage to the learning management systems [45][46][47] which has brought about the growth of the LMS in major parts of the world and has boosted the perceived usefulness and ease of use of users to achieve satisfaction and delivery of its purpose [15], [19] as LMS stands as the only means to continue education process without delays. Before the COVID-19 pandemic, LMS was considered a waste of time as it is less preferred than attending lectures in classes [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating learners' performance and determining assignments and class duties [33][34][35][36]. Despite this role that the teacher plays, there are some difficulties that he faces in working with the cooperative educational system, as the group's opinions may be divided during the discussion, and the teacher will have to choose one side of it, so the other side will be frustrated and uncomfortable [37,38].…”
Section: The Role Of the Teacher (Professor) In Cooperative Educationmentioning
confidence: 99%